Perceived descriptive safety-related driving norms within and outside Arab towns and villages in Israel. (2nd January 2016) - Baron-Epel, Orna; Obid, Samira; Fertig, Shahar; Gitelman, Victoria
ABSTRACT: Objective: Involvement in car crashes is higher among Israeli Arabs compared to Jews. This study characterized perceived descriptive driving norms (PDDNs) within and outside Arab towns/villages and estimated their association with involvement in car crashes. Methods: Arab drivers (594) living in 19 towns and villages were interviewed in face-to-face interviews. The questionnaire included questions about involvement in car crashes, PDDNs within and outside the towns/villages, attitudes toward traffic safety laws, traffic law violations, and socioeconomic and demographic variables. PDDNs represent individuals' perceptions on how safe other people typically drive. The low scores indicate a low percentage of drivers performing unsafe behaviors (safer driving-related norms). A structural equation modeling analysis was applied to identify factors associated with PDDNs and involvement in car crashes. Results: A large difference was found in PDDNs within and outside the towns/villages. Mostly, the respondents reported higher rates of unsafe PDDNs within the towns/villages (mean = 3.76, SD = 0.63) and lower rates of PDDNs outside the towns/villages (mean = 2.12, SD = 0.60). PDDNs outside the towns/villages were associated with involvement in a car crash ( r = −0.12, P <.01), but those within the towns/villages were not. Within the towns/villages, attitudes toward traffic laws and PDDNs were positively associated with traffic law violations ( r = 0.56, P <.001; r = 0.11, P <.001 respectively), where traffic law violations were directly associated with involvement in a car crash ( r = −0.14, P <.001). Conclusions: Unsafe PDDNs may add directly and indirectly to unsafe driving and involvement in car crashes in Arab Israelis. Because PDDNs outside towns/villages were better, increased law enforcement within towns/villages may improve these norms and decrease involvement in car crashes.